Prevalence and predictors of low voltage zones in the left atrium in patients with atrial fibrillation. Issue 6 (10th June 2017) - Huo, Yan; Gaspar, Thomas; Pohl, Matthias; Sitzy, Judith; Richter, Utz; Neudeck, Sebastian; Mayer, Julia; Kronborg, Mads Brix; Piorkowski, Christopher
Abstract: Aims: To describe the extent and distribution of low voltage zones (LVZ) in a large cohort of patients undergoing ablation for paroxysmal and persistent atrial fibrillation (AF), and to explore baseline predictors of LVZ in these patients. Methods and results: Consecutive patients who underwent a bipolar voltage map guided AF ablation, were enrolled. Voltage maps were conducted for each patient using 3-dimensional electroanatomical mapping system and LVZ were defined as areas of bipolar voltage < 0.5 mV. A total of 539 patients (309 male, age 65 ± 10 years) were included. Low voltage zones was present in 58 out of 292 patients with paroxysmal and 134 out of 247 persistent AF ( P < 0.001). The area of LVZ was larger in patients with persistent as compare to paroxysmal AF, 5 cm 2 (IQR 3-18.6) vs. 12.1 cm 2 (IQR 3.6-28.5), P = 0.026, respectively. In the multivariate analysis age (OR 1.07, 95%CI 1.05-1.10, P < 0.001), female gender (OR 2.18, 95%CI 1.38-3.43, P = 0.001), sinoatrial node dysfunction (OR 3.90, 95%CI 1.24-12.21, P = 0.020), larger surface area of left atrium pr. cm 2 (OR 1.01, 95%CI 1.00-1.02, P = 0.016), and persistent AF (OR 5.03, 95%CI 3.20-7.90, P <0.001) were associated with presence of LVZ. Conclusion: In a large cohort of patients undergoing ablation for AF, the prevalence of LVZ was higher and LVZ areas larger in patients with persistent as compared with paroxysmal AF. The most frequent localization of LVZ was anterior wall, septum and posterior wall. Presence of LVZ was associated with higher age, female gender, larger LA surface area, and sinoatrial node dysfunction.